Zambia Wildlife Sector Policy : Situation Analysis and Recommendations for a Future Policy - Sichilongo, Mwape; Mulozi, Pamela; Mbewe, Biston; Machala, Chomba; Pavy, Jean-Michel (World Bank, Washington, DC, 2012)
Zambia is endowed with an abundance of natural resources that include, water, forests and wildlife. The country's wildlife resources are managed through government-supported National Parks and Game Management Areas (GMAs) and private sector game ranches. The main objective of this wildlife sector policy review is to consolidate the findings collected from an extensive bibliography published during the life of the current policy, and the analysis of key sector practitioners. The second objective is to analyze these findings with a view to formulating broad recommendations to inform the design of the new vision and new policy of the sector. This document aims to identify policy issues that would provide a basis for the creation of an enabling environment for the development of the wildlife sector as a growth sector according to the Sixth National Development Plan (SNDP) and the vision 2030. It contains five provisional priority recommendations that offer practical solutions and six strategic options which constitute policy objectives. In conclusion, an improvement of the policy framework could have a large impact on how people and wildlife relate and coexist in Zambia. This policy review confirmed that, while important policy measures are necessary, particularly for shared growth, the adoption of a forward looking wildlife policy and act will not be sufficient if it is not accompanied by unequivocal willingness on the part of Government to reorganize and strengthen Zambia Wildlife Authority's (ZAWA's) capacity and provide financing commensurate to its need.